PP21 Factors affecting community first responders' role in rural emergencies: a qualitative interview study. Issue 9 (23rd August 2022) - Patel, Gupteswar; Phung, Viet-Hai; Julie Pattinson, J; Trueman, Ian; Ørner, Roderick; Botan, Vanessa; Asghar, Zahid; Smith, Murray D; Ridyard, Colin; Rowan, Elise; Brewster, Amanda; Mountain, Pauline; et al.
Abstract : Background: Community first responders (CFRs) are volunteers delivering emergency medical assistance and maintaining a patient's condition until an ambulance arrives. Previous research has highlighted the CFR role and relationships, motivations, practice and perceptions, and need for mental health support. However, factors influencing CFR practise in the field are a relatively underexplored area. We aimed to explore the factors embedded in CFR implementation processes that either facilitated or hindered CFRs' activities and practice in the UK. Method: In a qualitative study, we conducted interviews with CFRs and CFR leads, paramedics and ambulance clinicians, commissioners, patients and relatives across six English ambulance service regions. Thematic analysis, supported by NVivo, enabled the identification codes and themes. Result: Overall, 47 participants were interviewed including CFR leads (15), CFRs (21), ambulance staff (4), and commissioners (2) from six ambulance services with patients and relatives (5) from the same regions. The findings revealed multi-layered factors influencing effective CFR functioning at three levels, namely individual, institutional, and societal. CFRs' local expertise helped them to navigate operational challenges. Use of a personal vehicle and navigation software aided CFRs' ability to respond promptly. Continuing training improved CFRs' skills. CFR functioning was facilitated by positive relationships with ambulance crews. Identification and recognition by patients were important and aided by wearing uniforms. Community support was a facilitator for CFR activities in rural areas. In contrast, limited communication in remote regions, long waits for an ambulance, and reliance on community donations impeded CFRs' care function. Volunteer shortages and lack of access to a blue light while using trusts' car hindered CFRs' ability to respond quickly. Negative relationships with ambulance crews also hampered CFRs' involvement. Conclusion: This study highlights factors associated with effective CFR functioning and the requirement for supportive institutional and societal contexts for CFRs to assist patients in medical emergencies.